Futsal 2018 national league: analysis of the gols incidence - Moraes, Guilherme Armando de (2020)
This study aims to analyze the frequency of goals of the Futsal matches of the 2018 National Futsal League. We analyzed 1122 goals that occurred in 194 matches of the 2018 National Futsal League, in male adult category. The goals were divided into 4 periods of 5 minutes in each playing time, being 1st period (0:00 to 5:00 minutes), 2nd period (5:01 to 10:00 min.); 3rd period (10:01 to 15:00 min.) and 4th period (15:01 to 20:00 min). Frequencies (absolute and relative), mean and standard deviation were used to describe the study variables. The results show that the average of goals was higher at the end of the game compared to the other periods and the home games influenced the occurrence of goals in the 2018 Futsal League. It is concluded that futsal requires technical attention , tactics and physics in the final minutes of matches  when the highest number of goals occurs, becoming the reorganization of training of these aspects of teams, in order to minimize this phenomenon and prevent the end result of the game being compromised.